Retinol-binding protein-4 expression marks the short-term mortality of critically ill patients with underlying liver disease: Lipid, but not glucose, matters - Wei-Ting Chen (Nature Portfolio, 2017)
Abstract The implications of retinol-binding protein-4 (RBP4) expression in critically ill patients with underlying liver diseases remain unclear. A prospective cohort study involving 200 liver intensive care unit (ICU) patients was conducted, with 274 blood donors as controls. Patient outcomes were assessed using Cox and Kaplan-Meier analyses. Of the 200 ICU patients (mean age: 56.0 yrs), 79.5% were male, 72.5% were cirrhotic, 62% were septic, 29.5% were diabetic, and 29% expired in the ICU (median admission: 7.5 days). ICU patients had lower baseline RBP4 (25.6+/−18.4 vs. 43.8+/−35.0 mg/L, p < 0.001) and total cholesterol (TC) levels than controls. The surviving ICU patients had lower baseline international normalized ratios (INRs) of prothrombin time, model for end-stage liver disease (MELD) scores and sepsis rates, but higher estimated glomerular filtration rates (eGFRs) and RBP4 levels than non-surviving patients. eGFRs, INRs and TC levels were independently associated with RBP4 levels. Only surviving patients exhibited significantly increased RBP4 levels after ICU discharge. Baseline RBP4 levels and MELD scores predicted 21-day (≤10 mg/L) and 1-year (≥25) mortality, respectively. In critically ill patients with underlying liver disease, with a link to eGFRs, INRs and TC levels, the baseline RBP4 may serve as a marker for short-term mortality.